2015
DOI: 10.1002/jso.24123
|View full text |Cite
|
Sign up to set email alerts
|

The importance of surgical margins in primary malignancies of the liver

Abstract: Resection is an important treatment modality for hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC). Anatomic resection is generally preferred for HCC. When anatomic resection is not feasible, prospective data have demonstrated an improved outcome among HCC patients who have a resection with wide versus narrow surgical margins. Similarly, among patients with ICC, R1 resection has been associated with worse outcomes. In addition, margin width may also impact risk of recurrence and survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 82 publications
0
32
0
1
Order By: Relevance
“…However, the relationship between the surgical margin and the oncologic outcome is unclear in patients with HCC [5]. Although sufficient margin from the tumor is the principle of oncologic surgery, most patients with HCC have chronic liver disease or cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the relationship between the surgical margin and the oncologic outcome is unclear in patients with HCC [5]. Although sufficient margin from the tumor is the principle of oncologic surgery, most patients with HCC have chronic liver disease or cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between resection margin (RM) and disease recurrence is unclear. Some studies have shown that the oncologic outcomes were better in patients with a wide RM than in patients with a narrow RM; however, other studies revealed no oncologic benefits of a wide versus narrow RM [5-7]. …”
Section: Introductionmentioning
confidence: 99%
“…But in recent years, the indication was extended to those recipients over Milan criteria. In fact, there are no worldwide recognized selection criteria for LT. Due to the invasive and metastatic nature of HCC, recurrence is still the main problem after liver resection4. Patients with intrahepatic recurrence would be given an accurate assessment, and considered for salvage liver transplantation (SLT)5.…”
mentioning
confidence: 99%
“…Several previous studies indicated that a resection margin of more than 1cm is an independent factor of improved recurrence-free survival[39-42]. But whether it can benefit all HCC patients is still controversial[43-47]. The clinical definition of centrally located HCC emphasizes the vicinity of liver tumor with major vascular structures.…”
Section: Surgical Determination and Resection Marginmentioning
confidence: 99%